Flat strips. A case presentation. - Margarita Espinosa Jiménez; Virginia Pentón García (Medisur)
This research paper presents a case of a 12 year old . Give with Angle´s Malocclusion class II, division I, with a 10 mms protuberance and an overpass of complete crown to whom a functional device with plane trail was applied . At 8 months follow up molar relation class I , a 4 mms protuberance and an overpass of the third part of the crown is observed. These results have been assessed as a satisfactory evolution of the patient.